DIGITAL CURATION DI UPT PERPUSTAKAAN JENDERAL SOEDIRMAN - Kurniawan, Aris; Supriyana, Supriyana; Saino, Saino; Enimawati, Dwiana; Susiach, Susiach (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2018)
This study discusses the digital curation in Unsoed Library Unit. Digital curation is an ongoing process of digital collection management activities. The purpose of this research is to know the process of management and handling of digital collection of thesis in terms of Digital Curation Center (DCC) Life Cycle Model. The benefits of this research are as material evaluation of the management of digital document objects, and as reference in the formulation of policies and legal basis needed in the management of digital collections in Unsoed Library Unit. This research uses descriptive qualitative method that is by doing depiction using word and language from perception and action performed by librarian. Based on the data obtained through interviews, expert observation and consultation, digital curation cycle already exists in Unsoed Library Unit. However, there is still a need to strengthen the legal basis, renewal of standard operating procedures, facilities, and understanding of digital curation.